Signifikansi Metode Deduktif dan Induktif dalam Pembelajaran Ilmu Nahu - Ritonga, Ade Muhammad (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
Nahu rules (Nahu science) are one of the branches of Arabic linguistics, considering the importance of understanding Nahu science in learning Arabic, but it is very unfortunate that there are still many students who are less able to understand the rules of Nahu science itself, so appropriate methods are needed. in his learning. In learning science, there are two methods that are often used, namely deductive and inductive methods, but the significance of these two methods needs to be studied. Therefore, this article will discuss the significance of deductive and inductive methods in learning science. This article was written using the library research method, the data obtained as a reference in writing were in the form of books, articles and several other sources of data or information that were considered relevant to the study. The results of this research show that deductive and inductive methods are still frequently and relevantly used in learning science, especially in Indonesia. Where there are still many Islamic boarding schools and madrasas that use books such as Al-ajrumiyah, nahu Wadih and Syarah Ibn 'aqil in learning nahu science. And these books still use deductive and inductive methods in their teaching.